Od dyktatury do demokracji: ewolucja systemu wyborczego Hiszpanii - Jaroszyk-Pawlukiewicz, Joanna (Przegląd Politologiczny, 2018)
After 1975 Spain began the difficult process of transforming its political system. The changes included the electoral system, but rather than only reconstructing the system, the principles of how to elect the representatives of the Spanish nation were stipulated anew. Therefore, the paper attempts to answer the question of whether the solutions adopted fully reflect the principle of national representation, as intended by their authors. It is also necessary to present the proposals to reform the Spanish electorate system suggested by Spanish academia.